Hemorragia Subaracnoideia e Angiografia Cerebral por Tomografia Computorizada - Santos, N (2011)
We present a review of 57 cases of nontraumatic subarachnoid hemorrhagesubmitted to CT angiography of the cerebral vessels. The purpose of our study was to estimate the value of CT angiography in the detection of intracranial aneurysms. These findings were compared with those from selective angiography. The results showed that CT angiography is a rapid, low-risk technique with a low level of invasiveness and high specificity and sensitivity in the detection of cerebral aneurysms, allowing the planning of endovascular intervention and surgical approach.